Huaier Aqueous Extract Inhibits Ovarian Cancer Cell Motility via the AKT/GSK3β/β-Catenin Pathway - Yan, Xiaohui; Lyu, Tianjiao; Jia, Nan; Yu, Yinhua; Hua, Keqin; Feng, Weiwei (PLOS ONE, 2013)
Traditional Chinese medicine has gained popularity due to its ability to kill tumor cells. Recently, the apoptotic and anti-angiogenic effects of Trametes robiniophila murr (Huaier) have been investigated. The aim of this study was to investigate its effect on cell mobility and tumor growth in ovarian cancer. Cell viability and motility were measured using SRB, scratch and migration assays. Cell apoptosis was analysed by annexin V/PI staining. Using a reverse-phase protein array (RPPA) assay, we analyzed the levels of 153 proteins and/or phosphorylations in Huaier-treated and untreated cells. Huaier inhibited cell viability and induced both early and late apoptosis in SKOV3, SKOV3.ip1 and Hey cells in a time- and dose-dependent manner. Cell invasiveness and migration were also suppressed significantly. The RPPA results showed significant differences (of at least 30%; P <0.05) in the levels of 7 molecules in SKOV3 cells and 10 in SKOV3.ip1 cells between the untreated and treated cells. Most of the molecules identified play roles in cell proliferation, apoptosis or cell adhesion/invasion. Western blot analysis further validated that Huaier treatment resulted in decreased AKT phosphorylation, enhanced expression of total GSK3β, inhibition of the phosphorylation of GSK3β on S9, reduction of both cytoplasmic β-catenin expression and nuclear β-catenin translocation, and transcriptional repression of several Wnt/β-catenin target genes (DIXDC1, LRP6, WNT5A, and cyclin D1). After knocking down GSK3β, β-catenin expression could not be inhibited by Huaier. Finally, Huaier inhibited the growth of ovarian tumor xenografts in vivo. These studies indicate that Huaier inhibits tumor cell mobility in ovarian cancer via the AKT/GSK3β/β-catenin signaling pathway.